THE ROLE OF RELIGIONS IN POST-SOVIET COUNTRIES AND EXAMPLES OF THEIR RELATIONS WITH STATES - Giorgi Pareshishvili (International Journal of Innovative Technologies in Social Science, 2024)
It should be noted that the constitutional requirements for the regulation of freedom of religion and the issues of determining the relationship between the church and the state were not highlighted in the Soviet system. From the declaratory point of view, the constitutions of this country were partially similar to the constitutions of the West, which allowed their reception in the constitutions of national states even after the communist regime. In the communist space, the freedom of religion was considered from atheistic positions, and Ro-Gortz Luchterhandt in his work "Development of religious legislation in Eastern Europe" would say: the communist system is a state system hostile to religion. The hostility to religion began with a claim to science. This was also supported by the anti-religious and atheistic understanding of freedom of conscience. Freedom of conscience was not a legally guaranteed autonomy for each individual to choose according to custom and religious responsibility in favor of what is truly known. It rather meant freedom of conscience from religion. Because of such doctrines, religion was displaced from public life into private life.